(untitled) (Modern education and development, 2025)
This article explores effective methodological approaches to teaching English to preschool children. It emphasizes the importance of age-appropriate strategies such as the use of visual aids, songs, Total Physical Response (TPR), storytelling, and interactive games. The paper outlines how these techniques align with the cognitive and emotional development of young learners and highlights the teacher’s critical role in fostering a supportive and engaging language environment.